Pengaruh Program Diskon Terhadap Keputusan Pembelian - Fadillah, Adil; Syarif, Rini (LPPM Institut Bisnis dan Informatika Kesatuan, 2013)
In the implementation of products marketing, a company is usually bound to use marketing concept of product, price, place, and promotion to achieve marketing goal. Promotion supports marketing activities in order that the marketing programs will be able to proceed as expected. The purpose of this study is to determine which types of discount programs implemented by the company, to find out the factors influencing purchase decision by consumers, and to know the effect of discount program on purchasing decision at PT Ramayana Bogor Trade Mall. Data analysis technique used by the author is statistical analysis , i.e. simple linear regression analysis, simple linear correlation coefficient, and hypothesis test. Based on the analysis, it’s gotten simple linear regression equaty. Contant 30,451 states that if there is no discount program, the purchasing decision will be 30,451. Coefficient regression 0,148 states that any additional increase/decrease in discount program for a unit will result an increase/decrease of dependent variable (Y) as high as 0,148, with constant as high as 30,451. The correlation between discount variable and purchasing decision variable counted by using correlation coefficient is o,161 or 1,6%. This shows that there is a very low correlation between discount program and purchasing decision. Based on hypothesis test, t-statistics obtained from t-table is 1,695, while t-table is 1,645. Therefore, t-statistics > t-table (1,695 > 1,645 at α = 0,05), with the result that Ho is refused and H1 is accepted. Thereby discount program influences purchasing decision insignificantly. Significance level of correlation coefficient yields figure 0,110. Because of probability is above 0,05, the correlation between discount program and purchasing decision is not significant. It’s found out that r-square coefficient is 0,026 or 2,6%, the rest is 97,4%, due to other causes which are not observed by the author. It shows that there is low correlation between discount variable and purchasing decision. Based on this analysis it can be concluded that discount program has no significant correlation toward purchasing decision. Keywords:discount program; purchasing decision